Pengaruh Penerapan Asesmen Diagnostik Terhadap Semangat Belajar Siswa Kelas IV MI Ma'arif Ketegan Sidoarjo - Nurul Hidayah; M. Amin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Diagnostic assessment is a process for measuring students' abilities or skills so that they can provide important information to teachers so that teachers can determine and provide learning that is appropriate to students' learning models and increase students' enthusiasm and academic achievement. Research on the influence of assessment on students' enthusiasm for learning is very necessary. This is an urgency in the world of education. The reason the researchers made MI Maarif Ketegan Sidoarjo the object of research was because MI Maarif Ketegan was one of the 5 MIs that had a decree to implement the independent curriculum. Apart from that, researchers also saw that the facilities and infrastructure, educational staff and other supports were very good. This research is correlation research with a quantitative approach. In this research, researchers did not take action to prove the effectiveness of a strategy, method, or media. However, researchers used an alternative that contained several questions aimed at students. The questions included are questions with yes/no answers with a total of 10 questions. Based on research conducted on June 9 2023, researchers found that with a percentage of 94% of students having a final learning score in the